(untitled) (Journal of Mathematical Study, 2017)
In this paper, we use Pacard-Xu's methods to discuss the complex deformation of constant scalar curvature metrics in the case of fixed and varying complex structures. Moreover, we also discuss the complex deformation of Kähler-Ricci solitons.